Effect of caffeine supplementation on anaerobic and aerobic performance in sleep-restricted male college soccer players - Cheng, R.; Wang, N.; He, W.; Zhou, Z.; Chen, Z.; Li, X. (Frontiers in Physiology, 2025)
This study aimed to explore the effects of sleep restriction of =5 h within 24 h on anaerobic and aerobic performance in male college soccer players and evaluated the effects of acute supplementation of 3 mg·kg-1 caffeine on the aerobic and anaerobic performance of college male soccer players under sleep restriction.